PENGARUH PENERAPAN MEDIA KARTU POSITIF DAN KARTU NEGATIF PADA MATERI OPERASI HITUNG BILANGAN BULAT TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VI SDN 232 INPRES MARUSU KAB. MAROS - Masna; Nursalam; Suarti (Primer Edukasi Journal, 2024)
This study aims to find out (1) The learning outcomes of students before the application of positive card and negative card learning media on integer arithmetic operations at SDN 232 Inpres Marusu, Maros Regency, (2) Student learning outcomes after applying positive card and negative card learning media to integer arithmetic operations at SDN 232 Inpres Marusu, Maros Regency, and (3) Are there differences in learning outcomes before and after the positive card and negative card media are applied to the integer arithmetic operations sub-theme at SDN 232 Inpres Marusu. The type of research used in this research is pre-experimental with the design "One Group Pretest-Posttest". The total population in this study were all students in class VI at SDN 232 Inpres Marusu, totaling 20 people. The instrument used in this research is the learning achievement test. The analysis technique used is descriptive statistical analysis and inferential statistics. The results of the analysis show that the average value of learning outcomes before using positive negative card media is 72.15 in the high category. While the average value of learning outcomes after being taught using negative positive card media of 92.44 is in the very high category. The results of the hypothesis test show that there are differences in learning outcomes before and after being taught using positive and negative card media, when viewed from the average post-test learning outcomes that are greater than the pre-test scores. So the application of positive negative card media has a positive influence on the results of learning mathematics theme for addition and subtraction arithmetic operations in class VI students at SDN 232 Inpres Marusu, Maros Regency. The implication of the research is that teachers who teach mathematics subject matter of addition and subtraction operations on integers are expected to be able to use positive and negative card learning media as an alternative way to improve students' mathematics learning outcomes